2016
DOI: 10.14419/ijsw.v5i1.6965
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study: bench-scale surfactin production from bacillus subtilis using analytical grade and concentrated glycerol from the biodiesel industry

Abstract: The market price of glycerol worldwide tends to decrease, since it is a by-product of biodiesel production. Thus its biotechnological use might lead to significant reduction in the cost of fermentations. The aim of this study was to compare the production of surfactin in peptone culture media supplemented with analytical grade glycerol (AGG) and concentrated glycerol from biodiesel production (CGBP). Differences were observed between the two processes including cell growth and dissolved oxygen consumption. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
2
0
4
Order By: Relevance
“…Hence, different alternative media, mostly based on agroindustrial residues, have been suggested as possible routes to decrease the surfactin production cost. Raw glycerol from the biodiesel industry has been suggested as a medium basis for surfactin production, resulting in a surfactin yield in the range of 71–286 mg/L [ 65 , 66 ]. Brewery wastewater, as a surfactin production medium, resulted in a surfactin yield of 6.6 mg/L [ 67 ], while distillers’ grains applied as a substrate gave a better result, with a yield of 1.04 g/L [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, different alternative media, mostly based on agroindustrial residues, have been suggested as possible routes to decrease the surfactin production cost. Raw glycerol from the biodiesel industry has been suggested as a medium basis for surfactin production, resulting in a surfactin yield in the range of 71–286 mg/L [ 65 , 66 ]. Brewery wastewater, as a surfactin production medium, resulted in a surfactin yield of 6.6 mg/L [ 67 ], while distillers’ grains applied as a substrate gave a better result, with a yield of 1.04 g/L [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Design of experiments is often employed to investigate the influence of different substances on surfactin productivity [63]. While most published results are based on synthetic media such as mineral salt medium with glucose as carbon source, also cultivations based on alternative substrates such as cashew apple juice, cassava flour, whey or glycerol from biodiesel industry were investigated [64][65][66]. Such research aims at both increasing the surfactin yields, while lowering the overall production costs by using by-products or agricultural/food processing waste streams.…”
Section: Improvement Of the Medium Compositionmentioning
confidence: 99%
“…A literatura reporta uma grande diversidade de substratos utilizados como fonte de carbono para a produção de surfactina, tais como glicerina residual (ANDRADE et al, 2017;SOUSA et al, 2014;CRUZ et al, 2018); melaço de cana de açúcar (ROCHA et al, 2020); polpa de sisal (ABADIA, 2015); suco de caju (FELIX et al, 2019) e manipueira (NITSCHKE et al, 2004;ANDRADE et al, 2016).…”
Section: Biossíntese De Surfactina Por Bacillus Subtilisunclassified
“…A Tabela 2 mostra alguns trabalhos recentes em que a glicerina residual é utilizada para a produção de surfactina. De acordo com Andrade et al (2017), a produção média de surfactina em meio mineral utilizando a glicose como substrato é em média 0,5 g/L.…”
Section: Biossíntese De Surfactina Por Bacillus Subtilisunclassified
See 1 more Smart Citation